CLINICAL-PATHOLOGICAL CHARACTERISTICS OF HORMONE INDEPENDENT LOBULAR BREAST CARCINOMA - Nikolić, Tamara; Ilic, Ivan; Jovicic Milentijevic, Maja; Nikolic, Nemanja; Stojanovic, Sara; Marinkovic, Marija; Stankovic, Milica; Milicevic, Aleksandar; Grujovic, Jelena; Petkovic, Nikola; Peric, Velimir; Nesic, Jovana; et al. (Acta medicae Medianae, 2022)
Estrogen has a role in the proliferation of luminal layer of epithelial breast cells and approximately 70% of human breast cancers have estrogen receptor expression. Based on the hormone receptor expression, we can classify these carcinomas as hormone-dependent and hormone-independent. Considering that the data in the world literature are incomplete, the aim of this research was a comparative analysis of these characteristics of hormone-dependent and hormone-independent lobular breast carcinomas. One hundred thirty-eight cases of lobular breast carcinomas were analyzed in relation to their hormonal status. Obtained morphometric values were subjected to statistical analysis using Student’s t-test and Fisher’s test. Statistically significant difference between groups of patients with hormone-dependent and hormone-independent lobular breast carcinomas was found for the age of patients (p = 0.036) and nuclear gradus (p = 0.006). On the other hand there was no statistically significant difference between two groups of patients considering the presence of metastasis in the axillary lymph nodes (p > 0.05). It was found that the patients with hormone-independent lobular breast carcinoma were significantly older then the patients with hormone-independent lobular breast carcinoma, and that expression of hormone receptors did not play a key role in metastasis of this carcinoma to the axillary lymph nodes.